Basic Principles and Stages of Treatment and Rehabilitation of Patients with Maxillary Palpebral Defects (Eurasian Medical Research Periodical, 2022)
Nowadays the main place in the rehabilitation system of the patients who have undergone the treatment for jaw neoplasms is occupied by the adequate prosthetics of the formed defects of the maxillofacial region. The use of modern prosthetic materials and alloys has opened up new possibilities in helping this contingent of patients. However, up to now not all medical institutions treating patients with tumours of the jaw fully use modern possibilities of providing therapeutic and rehabilitative help to them. One of the reasons is the lack of sufficient information about the role and place of orthopaedic dentist in the system of treatment measures in patients with this pathology. There are still cases where the surgeon operating on patients with jaw cancer has no direct contact with the orthopaedic dentist